2022
DOI: 10.1111/apa.16594
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and screen time in Swedish children and adolescents: The generation pep study 2018–2021

Abstract: Results from the Global Matrix 3.0, including 49 countries, found that physical activity levels of children and adolescents are low and screen time levels are high, with only 27%-33% and 34%-39% meeting the physical activity and screen time recommendations, respectively. 1 This is concerning as there is strong evidence of favourable associations in children and adolescents between total physical activity and adiposity, many cardiometabolic indicators, and bone health, as well as indications for favourable asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Our study found that high school students were less likely to be physically active for the recommended amount of time compared to middle school students. This is consistent with other studies that show a decline in physical activity with age [60,61]. In addition to this, students with a normal BMI are more likely to meet the recommended physical activity hours on weekends.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found that high school students were less likely to be physically active for the recommended amount of time compared to middle school students. This is consistent with other studies that show a decline in physical activity with age [60,61]. In addition to this, students with a normal BMI are more likely to meet the recommended physical activity hours on weekends.…”
Section: Discussionsupporting
confidence: 92%
“…This is concerning, especially when set in relation to the recent years increased engagement in obesogenic behaviors such as physically inactive and sedentary lifestyles [47,48] and dietary patterns characterized by high intakes of processed foods rich in salt and added sugars [49]. For instance, in Sweden, a significant increasing trend in screen time was observed in 4to-6-year-old children between 2018 and 2020, with a lower proportion of children watching < 1h of screen time per day [50]. In addition, an increased proportion of 4-to-6-year-old children that had 3-4 h of daily screen time was also observed [50].…”
Section: Determinants Of Childhood Overweight and Obesity And Types O...mentioning
confidence: 99%
“…For instance, in Sweden, a significant increasing trend in screen time was observed in 4to-6-year-old children between 2018 and 2020, with a lower proportion of children watching < 1h of screen time per day [50]. In addition, an increased proportion of 4-to-6-year-old children that had 3-4 h of daily screen time was also observed [50]. Furthermore, it is estimated that only 20% and 30% of Swedish preschool-age children reach the national recommendations of physical activity and intake of fruit and vegetables respectively [51,52].…”
Section: Determinants Of Childhood Overweight and Obesity And Types O...mentioning
confidence: 99%
“…However, in real-world scenarios, children are spending more time indoors in front of screens . Efforts to promote more physical activity outdoors are thwarted to some degree by parents and school administrators, especially in countries with highly competitive educational systems, such as China.…”
Section: Introductionmentioning
confidence: 99%
“…However, in real-world scenarios, children are spending more time indoors in front of screens. 6 , 7 Efforts to promote more physical activity outdoors are thwarted to some degree by parents and school administrators, especially in countries with highly competitive educational systems, such as China. Their major concern is that increased outdoor physical activity time will reduce studying time and hence compromise academic performance.…”
Section: Introductionmentioning
confidence: 99%